Update and critical appraisal of the use of topical azithromycin ophthalmic 1% (AzaSite®) solution in the treatment of ocular infections - Utine CA (Dove Medical Press, 2011)
Canan Asli UtineYeditepe University, Department of Ophthalmology, Istanbul, Turkey and Ocular Surface Disease and Dry Eye Clinic, Cornea and External Disease Service, The Wilmer Eye Institute, The Johns Hopkins University School of Medicine, Baltimore, MD, USAAbstract: Azithromycin is an azalide that acts by binding to the 50S ribosomal subunit of susceptible microorganisms and interfering with microbial protein synthesis. Azithromycin is also noted by anti-inflammatory and immunomodulatory activity. AzaSite® (Inspire Pharmaceuticals, Inc, Durham, NC) is azithromycin ophthalmic solution, 1% formulated in polycarbophil (the aqueous mucoadhesive polymer contained in DuraSite®) that delivers high and prolonged azithromycin concentrations in a variety of ocular tissues, including the conjunctiva, cornea and particularly the eyelid. AzaSite was approved by the Food and Drug Administration (FDA) in the US in 2007, for the treatment of bacterial conjunctivitis caused by susceptible isolates. This article aims to evaluate the peer-reviewed published scientific literature and to define well-established uses of AzaSite eye drops in the field of ocular infections.Keywords: azithromycin, AzaSite, DuraSite